The impacts of family involvement on general hospital care experiences for people living with dementia: An ethnographic study. (August 2019) - Kelley, Rachael; Godfrey, Mary; Young, John
Abstract: Background: A quarter of people in general hospitals have dementia. Limited existing studies suggest that hospital care experiences of people living with dementia, and the involvement of their families in care, may be suboptimal. Objectives: The objectives of this study were to explore how family involvement impacts upon experiences of hospital care for people living with dementia. Design: A qualitative ethnographic study. Methods: Ethnographic data were collected from two care of older people general hospital wards. Data were collected via observations, conversations and interviews with people living with dementia, families and staff. In total, 400 hours of observation and 46 interviews were conducted across two 7–9 month periods. Results: People living with dementia could experience a lack of connection on multiple levels - from pre-hospital life as well as life on the wards – where they could spend long periods of time without interacting with anyone. There was great variation in the degree to which staff used opportunities to involve families in improving connections and care. When used, the knowledge and expertise of families played a crucial role in facilitating more meaningful interactions, demonstrating how person-centred connections and care are possible in busy hospital settings. Despite such benefits, the involvement of families and their knowledge was not routine. Care was required to ensure that family involvement did not override the needs and wishes of people living with dementia. Conclusions: This study demonstrates the benefits of involving families and their knowledge in care, advocating for family involvement, alongside the involvement of people living with dementia, to become a more routine component of hospital care.